Economic Importance of Belgian Transport Logistics - Frédéric Lagneaux (National Bank of Belgium, 2008)
This paper is a publication issued by the Microeconomic Analysis service of the National Bank of Belgium. This is the outcome of a first research project on the Belgian transport logistics sectors. In the past few years, the logistics business has turned out to play a significant part in wealth creation in our country, whose economy is driven by services. This study can be seen as an extension of Working Paper No. 115 on Belgian ports, issued in May 2007, as the activities under review are closely tied to transport in general and maritime transport in particular. Considering that this is a first attempt to estimate the economic importance of Belgian transport logistics, it was decided to favour a sectoral approach, by focusing on some freight transport logistics sectors clearly defined in the NACE classification. The impact is presented in two parts: the direct effects and the indirect effects. Furthermore, a short analysis is provided about the economic impact of other activities, such as in-house logistics and European distribution centres. An overview of some developments per sub-sector is provided for the period 2000 - 2005, with the emphasis on 2005. The core of the analysis, which is statistical and therefore not based on a survey, looks more specifically into developments in terms of value added, employment, investment and the financial situation of the companies concerned. A first estimate of developments over the 2005 - 2006 period is also provided for value added and employment. Annual accounts data from the Central Balance Sheet Office are used for the calculation of direct effects, the study of financial ratios and analysis of the social balance sheet. Also worth mentioning is that the indirect effects of the activities concerned have been estimated in terms of value added and employment, on the basis of data from the NAI (National Accounts Institute). A comprehensive analysis of the linkages between the sectors under review and the other Belgian sectors is presented. The activities under review accounted for no less than 3.1 p.c. of Belgian GDP and 3.4 p.c. of the country's domestic employment in 2005. Including indirect effects, these percentages respectively amounted to 5 and 5.3 p.c. in the same year. Taking some survey data into account, the overall impact would reach roughly 8 p.c. of the Belgian economy, if transport logistics business provided by external branches on the one hand and in-house transport logistics on the other were added to these above-mentioned sectoral percentages. This report provides a comprehensive account of these issues, giving information per economic sector.
Keywords: C67; J21; L91; L92; L93; L96; R15; R34; R41; 330; Logistikdienstleister; Branchenentwicklung; Wirkungsanalyse; Belgien